Experimental and numerical study of the flow past the Olympic class K-1 flat water racing kayak at steady speed - Tzabiras, G. D.; Polyzos, S. P.; Sfakianaki, K.; Diafas, V.; Villiotis, A. D.; Chrisikopoulos, K.; Kaloupsis, S. (The Sport Journal, 2010)
Abstract: The present work is concerned with the study of the hydrodynamic performance of an Olympic class "K-1" flat water racing Kayak. The evaluation of the hydrodynamic resistance of the vessel is of major importance since it is directly related to the human power required to sustain a specific speed. In this respect, experiments in calm water and regular waves were conducted at various speeds past the particular boat at the towing tank of the Laboratory for Ship and Marine Hydrodynamics (LSMH) of the National Technical University of Athens (NTUA). The calm water tests were performed in the range of speeds from 0.25 to 5m/s and useful conclusions were drawn concerning the influence of the wave formation on the non-dimensional resistance coefficients. Experiments in regular waves were carried out for two characteristic speeds and showed an increase of the hydrodynamic resistance of about 11%. Furthermore, systematic numerical tests using advanced computer codes developed at LSMHE have been performed in order to investigate whether Computational Fluid Dynamics (CFD) tools can be applied with confidence for predicting the calm water resistance of similar vessels. The scope of this part of the investigation is related to a rapid and cost-effective optimization of the shape of the boat. The computed results for the total resistance were in satisfactory agreement with the measurements, thus forming a basis for further investigation and deeper understanding of the athlete-boat interaction, especially for high performance and competition boats.